The ability of genetically lean or fat slow-growing chickens to synthesize and store lipids is not altered by the dietary energy source. (11th May 2015) - Baéza, E.; Gondret, F.; Chartrin, P.; Le Bihan-Duval, E.; Berri, C.; Gabriel, I.; Narcy, A.; Lessire, M.; Métayer-Coustard, S.; Collin, A.; Jégou, M.; Lagarrigue, S.; et al.
Abstract : The increasing use of unconventional feedstuffs in chicken's diets results in the substitution of starch by lipids as the main dietary energy source. To evaluate the responses of genetically fat or lean chickens to these diets, males of two experimental lines divergently selected for abdominal fat content were fed isocaloric, isonitrogenous diets with either high lipid (80 g/kg), high fiber (64 g/kg) contents (HL), or low lipid (20 g/kg), low fiber (21 g/kg) contents (LL) from 22 to 63 days of age. The diet had no effect on growth performance and did not affect body composition evaluated at 63 days of age. Glycolytic and oxidative energy metabolisms in the liver and glycogen storage in liver and Sartorius muscle at 63 days of age were greater in chicken fed LL diet compared with chicken fed HL diet. In Pectoralis major (PM) muscle, energy metabolisms and glycogen content were not different between diets. There were no dietary-associated differences in lipid contents of the liver, muscles and abdominal fat. However, the percentages of saturated (SFA) and monounsaturated fatty acids (MUFA) in tissue lipids were generally higher, whereas percentages of polyunsaturated fatty acids (PUFA) were lower for diet LL than for diet HL. The fat line had a greater feed intake and average daily gain, but gain to feed ratio was lower in that line compared with the lean line. Fat chickens were heavier than lean chickens at 63 days of age. Their carcass fatness was higher and their muscle yield was lower than those of lean chickens. The oxidative enzyme activities in the liver were lower in the fat line than in the lean line, but line did not affect energy metabolism in muscles. The hepatic glycogen content was not different between lines, whereas glycogen content and glycolytic potential were higher in the PM muscle of fat chickens compared with lean chickens. Lipid contents in the liver, muscles and abdominal fat did not differ between lines, but fat chickens stored less MUFA and more PUFA in abdominal fat and muscles than lean chickens. Except for the fatty acid composition of liver and abdominal fat, no interaction between line and diet was observed. In conclusion, the amount of lipids stored in muscles and fatty tissues by lean or fat chickens did not depend on the dietary energy source.